Topographical and Local Time Dependence of Large Stationary Gravity Waves Observed at the Cloud Top of Venus. Issue 24 (23rd December 2017) - Kouyama, T.; Imamura, T.; Taguchi, M.; Fukuhara, T.; Sato, T. M.; Yamazaki, A.; Futaguchi, M.; Murakami, S.; Hashimoto, G. L.; Ueno, M.; Iwagami, N.; Takagi, S.; et al.
Abstract: The existence of large stationary gravity waves was discovered during Akatsuki's first observation sequence in 2015. In this study, the further detection of large stationary gravity waves in brightness temperature images over a 1.5 year period is reported. The waves periodically appeared mostly above four specific highland regions in the low latitudes when these regions were in the local afternoon. The wave amplitudes attenuated after the wave locations passed beyond the evening terminator, and the locations of the waves tended to slowly drift eastward over their lifetimes. The appearances of stationary waves depend not only on surface topography but also on latitude and local time, suggesting that solar heating during the daytime and atmospheric structure affected by solar heating may control the excitation and propagation of stationary waves. Plain Language Summary: The Japanese Venus satellite "Akatsuki" has repeatedly found large atmospheric waves with north‐south lengths, which sometimes reach more than 10, 000 km at the cloud top level on Venus (altitude 70 km). These waves have repeatedly appeared above the Venusian highlands in low latitudes, such as Aphrodite Terra. Interestingly, the waves appeared and became clearer each time the highlands passed from noon to evening; therefore, they can be regarded as "daily" Venusian phenomena. Despite westward wind speeds reaching 100 m s −1 at the cloud top level (known as atmospheric superrotation), the east‐west propagation speeds of the large waves were nearly zero, and the waves stayed above their initial locations (stationary). This means that the origin of the waves could be the highland terrains below. Because waves can transport energy via propagation, stationary waves may transport atmospheric energy from the lower atmosphere to the cloud top level and may affect the speed of the superrotation. The existence and regular appearance of the large stationary waves indicate a continuous interaction between the lower and upper atmospheres on Venus via wave propagation, which provides a novel perspective of the Venusian atmosphere. Key Points: Stationary gravity waves with large horizontal extent at the cloud top level of Venus have been repeatedly identified The locations of these waves show a clear connection to Venusian highlands, and wave amplitude depends on the local time at the highlands Monitoring of the stationary waves would bring information of the Venusian atmosphere along the wave propagation paths